Distribution and speciation of zinc,cadmium and cobalt in the Southern Ocean - Baars, Oliver (2011)
Iron is the main control on phytoplankton productivity and macro-nutrient biogeochemistry in the Southern Ocean. However other micro-nutrients may also influence aspects of phytoplankton productivity and macro-nutrient cycling in this region. Three prime candidates have been identified for this study: zinc (Zn), cadmium (Cd) and cobalt (Co). Zn and Co are metal centres in important enzymes, transcription factors and vitamins (B12). Cd, long thought to be solely a toxic element, has recently been found as a metal centre in marine carbonic anhydrases – key enzymes needed for the acquisition of inorganic carbon. Deep water formation in the Southern Ocean directly impacts the other ocean basins. In this area Zn and Cd incorporation in opal and calcite shells have been used as indicators to reconstruct past nutrient conditions and ocean circulation but many questions remain open with regard to the cycle of these elements in the water column. In this work I report the first basin wide field study of distribution and speciation for dissolved Zn and Cd in the Atlantic sector of the Southern Ocean. The study area covered two north-south transects along the Zero Meridian and across the Drake Passage. Free Zn and Cd concentrations increased by 2-3 orders of magnitude in surface waters south of the Subantarctic Front linked to upwelling deep waters. Metal specific organic ligands (logK’M’=9.0-10.5) were detected throughout the study area for Zn (L < 4 nM) and Cd (L < 1.2 nM). For Zn, these ligands were however nearly always saturated due to the presence of excess concentrations of dissolved Zn in the high nutrient waters south of the Polar Front. For Cd, a small ligand excess remained but in contrast to measurements in the Subantarctic Zone, no source of ligands were detected in surface waters south of the Polar Front. These observations strongly suggest that a major fraction of ligands in the Antarctic Ocean were not actively produced for acquisition but rather consisted of degradation products. Based on these ...